2002
DOI: 10.1002/art.10555
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage‐specific constitutive expression of TSG‐6 protein (product of tumor necrosis factor α–stimulated gene 6) provides a chondroprotective, but not antiinflammatory, effect in antigen‐induced arthritis

Abstract: Objective. To study the chondroprotective effect of constitutively expressed TSG-6 protein (tumor necrosis factor ␣-induced protein 6; Tnfip6) in cartilage, using antigen-induced arthritis (AIA) in mice.Methods. Transgenic mice constitutively expressing TSG-6 protein in cartilage were generated. Cartilage-specific constitutive expression of TSG-6 protein was confirmed by in situ hybridization, Western blot analysis, and immunohistochemistry. Control and transgenic mice were immunized with methylated bovine ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 64 publications
1
65
1
Order By: Relevance
“…The results of these in vivo experiments suggest that Tnfip6 plays a role in the control of leukocyte influx into arthritic joints (most likely via interference with CD44/HA-mediated adhesion events), and is involved locally in the protection of cartilage matrix from proteolytic damage through complex formation with the serine protease inhibitor I␣I (7,8). The most important message of our in vitro and in vivo studies is that Tnfip6 can directly modulate cell adhesion (36,37), PMN cell extravasation (Figures 2 and 7), and perhaps also, the 3020 SZÁ NTÓ ET AL production of proinflammatory mediators such as IL-6 ( Figure 5C).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The results of these in vivo experiments suggest that Tnfip6 plays a role in the control of leukocyte influx into arthritic joints (most likely via interference with CD44/HA-mediated adhesion events), and is involved locally in the protection of cartilage matrix from proteolytic damage through complex formation with the serine protease inhibitor I␣I (7,8). The most important message of our in vitro and in vivo studies is that Tnfip6 can directly modulate cell adhesion (36,37), PMN cell extravasation (Figures 2 and 7), and perhaps also, the 3020 SZÁ NTÓ ET AL production of proinflammatory mediators such as IL-6 ( Figure 5C).…”
Section: Discussionmentioning
confidence: 97%
“…The antiinflammatory properties of Tnfip6 have been mainly attributed to its ability to potentiate the antiplasmin activity of I␣I upon association with this protease inhibitor, leading to the subsequent downregulation of the activity of a number of matrixdegrading proteases (7)(8)(9)(10). However, a recent study (11) found that the isolated Link module domain of Tnfip6, which lacks the ability to associate with I␣I, could still inhibit the influx of neutrophils to the site of inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It also stimulates the proliferation of vascular smooth muscle cells [34], and TSG-6 has been detected in the inflamed blood vessel walls of RA and OA synovium [2]. In addition, TSG-6 has anti-inflammatory effects in vivo, being a potent inhibitor of neutrophil migration [7,32], and it has been found to be chondro-protective in mice models of arthritis [8,21]. Since angiogenesis and inflammation are both believed to be significant in disc herniation patients with sciatica [22], we hypothesised that TSG-6 could be important in the aetiopathogenesis of this disorder.…”
Section: Introductionmentioning
confidence: 99%